Survei Pilihan Karir Ditinjau dari Profil Kepribadian DISC Pada Calon Karyawan PT. X Indonesia - Dian Juliarti Bantam (JURNAL PENELITIAN PENDIDIKAN, PSIKOLOGI DAN KESEHATAN (J-P3K), 2020)
This study aims to identify the career choice of prospective employees at PT. X Indonesia, which is reviewed by the personality profile mapping. This research is a survey that involving 211 subjects, in which the personality profile is measured using the DISC test. The results showed that prospective employees of PT. X Indonesian who have dominant personality type D are 15 subjects (7,11%), dominant personality type I are 13 subjects (6.16%), dominant personality type S are 92 subjects (43.60%) and the last personality dominant type C as many as 91 subjects (43.13%). In addition, the results also show that there are 17 career choices and dominant personality types. Account Managers, Contact Centers, Drivers, Online Sales Officers and Receptionists have the dominant type S. Admin, Branding and Communication Manager, Finance and Accounting, Web Developers, and Human Resources Operations, have dominant type C. There are also Business Development, Graphic Designer, Office Boy, Telemarketing and Recruitment Staff have dominant type S and type C. Meanwhile, Chemist Assistant has dominant type D and C, and Sales Manager with dominant type D, type S and type C.